The Effect of Human Resource Management Strategies on Employee Welfare at Bank Jateng - Rosidah Firnanda; Muafi (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to explore the influence of human resource management (HRM) strategies on employee well-being at PT Bank Pembangunan Daerah Jawa Tengah (Bank Jateng). Using a qualitative exploratory-descriptive approach, data were collected through in-depth interviews, observations, and documentation of the company's annual report. The results indicate that Bank Jateng has successfully built a robust well-being ecosystem through an integrative HRM strategy, which positions employees as human capital. The main strategies implemented include internalizing the "Gemilang" (Agile, Agile, Developing) organizational culture, implementing the 70:20:10 competency development model, and digital transformation through the E-Nawala system for administrative efficiency. Field findings revealed a high level of employee satisfaction with the remuneration system and financial well-being facilities, particularly the provision of employee loans with special, very low interest rates (3.76% - 5.50%). In addition, organizational support through open discussion spaces and limiting overtime until 9:00 PM WIB positively contributed to psychological well-being and work-life balance. This study concludes that human-oriented HR strategies have been proven to significantly increase employee loyalty and performance to support the sustainability of regional banking businesses.